STRATEGI PEMASARAN PRODUK BARU (STUDI KASUS PUDING LAMOTA) - Suprianto Naim; Hasdita Elies Ramadani; Elisa Juniarti; Mia Maelani; Elliza Rizki Wandani; Elsa Rahmawati (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
New products include new-to-the-world products that create new markets, minor product developments, or revisions to existing products. Sales of products, especially new products, require future-oriented marketing. Therefore the company must have a good marketing strategy for each new product that is produced where the strategy needs to be planned by taking into account the determinants of the success of new products on the market. Several new product marketing strategies, namely the S–O Strategy based on strength and opportunity considerations, consist of strategies prioritizing product quality, online marketing (online marketing), online competition, discounts, and giveaways. The W–O strategy is based on consideration of weaknesses and opportunities, consisting of market analysis strategies, attractive packaging, reviews or testimonials, and collaboration with business partners. The S–T strategy is based on consideration of strengths and challenges, consisting of strategies to maintain product quality and taste, maintain affordable product prices, and seek alternative quality raw materials when raw material prices rise. The W–T strategy is based on the consideration of weaknesses and challenges, consisting of research and development strategies, patenting product names, excellent service, and product evaluation.